Binder effect on ZnAl2O4-containing high-alumina refractory castables. Issue 8 (15th April 2022) - Pinto, V.S.; Luz, A.P.; Borges, O.H.; Pandolfelli, V.C.
Abstract: In situ spinel (MgAl2 O4, ZnAl2 O4, etc.) formation in alumina-based castables has been pointed out as a key issue in the refractory area, as it may enhance the mechanical properties and corrosion resistance of such materials. Nevertheless, the generation of these compounds is usually accompanied by a large volume expansion, which may induce crack formation in the resulting microstructure. Aiming to investigate the influence of zinc and magnesia spinel generation on the properties of alumina-based castables, three vibratable compositions, containing calcium aluminate cement or hydratable alumina as binders, were designed and characterized in this work. Different experimental tests were carried out to analyze the produced samples, such as: cold flexural strength, apparent porosity, hot elastic modulus, assisted sinterability, corrosion cup-tests, etc. According to the results, ZnAl2 O4 was mainly formed above 800 °C, favoring an earlier sintering of the samples. The addition of high amounts of ZnO or MgO (3 wt% to 9.4 wt%) to the castables resulted in the expansion of the samples during their first thermal treatment up to 1500 °C, reaching dL/L0 values equivalent to 1.16% up to 2.35%. Thermodynamic simulations indicated that spinel phase presented higher chemical stability when in contact with the evaluated synthetic slag at 1500 °C. Depending on the corrosion cup-test procedure (free or under constraint), different results of the slag infiltrated area were obtained (13.7%–20.5%) and, the combination of two different spinel phases (MgAl2 O4 and ZnAl2 O4 ) in a castable composition resulted in a refractory with enhanced corrosion behavior when the tests were carried out under constraint.